Development of Discovery Learning-Based Science Supplementary Textbooks to Improve Students' Creative Thinking - Adya Rosa; Alben Ambarita; Lilik Sabdaningtyas; Dwi Yulianti (STAI Hubbulwathan Duri, 2021)
Students' inability to think creatively in scientific classes is the impetus for this study. An appropriate Discovery Learning-based Science Supplement Textbook is the goal of this research, as is a description of its ability to boost students' creative thinking on Heat and Transfer Themes. Borg Gall's theory is the basis for research and development. The study's target audience was fifth-graders in Metro Timur District elementary schools. Using the purposive sampling method, 28 students from class V were selected for the study. Mixed quantitative and qualitative methods were used in the data analysis process. The Discovery Learning-Based Science Supplement Textbook was found to be practicable and useful in enhancing students' creative thinking abilities. The validation results of material experts, media experts, and linguists may conclude that the project is feasible. According to the experimental class's pre-and post-test scores of creative thinking, the category